Asset Management for Infrastructure Systems (Energy and Water) - Balzer, Gerd (Springer, 2015)
The implementation of competition in the area of infrastructure has often led to the consequence that within utilities, new decision-making and organizational structures were developed and installed. Here, the term “Asset Management” has been established in recent years, particularly in the area of technical as well as economic considerations. Globally considered, the essential task is to optimize the financial and operational tasks of an infrastructure system. In this context, the examples presented in this book often refer to the area of the electric power supply, but this should be considered only exemplary, as all considerations can be applied to other infrastructure sectors (gas, water, telecommuni cations, etc.). The principles and examples, which are presented in the following sections, essentially have two different sources, which in turn refer to the international discussion in companies, organizations, and associations:...